Strength variation characteristics of waste tailings cemented backfill materials with ultrafine particles - Deng, Daiqiang; Wang, Ye; Liang, Yihua; Fan, Jinkuan; Gao, Yu; Ma, Yunfan (Frontiers in Materials, 2023)
This study investigates the use of self-produced solid waste in mines to backfill the goaf, with energy saving and emission reduction technology requirements. Using a relevant backfill mixing proportion test and mechanical property test, we analyzed the strength variation law of backfill materials under different concentrations and cementation powder addition. The results showed that, for backfill materials at 7 days with an ash-tailings ratio of 1:6, the strength of specimens with 52% and 49% prepared concentrations, respectively, increased by 1.361 and 1.266 times over specimens with 49% and 46% concentrations. For backfill materials with 49% prepared concentrations and ash-tailings ratios of 1:6, 1:9, and 1:12, the specimen strength of the backfill materials with ratios of 1:6 and 1:9 improved by 0.616 MPa and 0.321 MPa—109.28% and 114.6%, respectively—compared with 1:9 and 1:12 backfill materials at 60 days. It is thus evident that the quantity of binding materials added plays a critical function in improving the strength of backfill materials, and in the subsequent application of goaf backfill. The strength of backfill materials can be enhanced by improving the gradation of backfill aggregates and increasing the amount of binding materials so as to achieve cost reductions and sustainable development.